2016
DOI: 10.1053/j.gastro.2016.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Bacteria From Patients With Celiac Disease and Healthy Subjects Distinctly Affect Gluten Breakdown and Immunogenicity

Abstract: Small intestinal bacteria exhibit distinct gluten metabolic patterns in vivo, increasing or reducing gluten peptide immunogenicity. This microbe-gluten-host interaction may modulate autoimmune risk in genetically susceptible persons and may underlie the reported association of dysbiosis and CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
158
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(186 citation statements)
references
References 50 publications
4
158
0
10
Order By: Relevance
“…Early on, it was hypothesized that CD is a digestive disorder that is caused by enzyme deficiencies (reviewed in reference 27). Our new findings in saliva, and the previous work on feces (23,24), show enhanced and altered bacterial gluten degradation in CD, suggesting that enzymatic processing may play an auxiliary role in CD pathogenesis. Gluten processing by microorganisms colonizing the oral cavity may be particularly relevant.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Early on, it was hypothesized that CD is a digestive disorder that is caused by enzyme deficiencies (reviewed in reference 27). Our new findings in saliva, and the previous work on feces (23,24), show enhanced and altered bacterial gluten degradation in CD, suggesting that enzymatic processing may play an auxiliary role in CD pathogenesis. Gluten processing by microorganisms colonizing the oral cavity may be particularly relevant.…”
Section: Discussionsupporting
confidence: 72%
“…Partial digestion may be highly relevant, however, from the perspective of how gluten is being presented further downstream in the gastrointestinal tract. Recently, it was demonstrated in a CD mouse model that gluten was partly digested by Pseudomonas aeruginosa, which liberated smaller peptides that were then more easily translocated through the mouse intestinal barrier and fueled disease activity (24). Analogously, oral microbial enzyme activities may likewise contribute to liberating more immunogenic gluten peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the severity of gluten immunopathology in NOD/DQ8 mice is influenced by the microbiota with which these mice are colonized and that administration of recombinant L. lactis expressing elafin can attenuate the inflammatory response of the host to gluten (12,23,24). Serpins are produced by a wide range of organisms and play a key role in maintaining immune homeostasis (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, Lactobacillus spp. have the capacity to degrade gluten resulting in decreased immunotoxicity of its major immunogens such as the 33-mer of alpha-gliadin [76]. At the same time, however, the full pathogenic potential of dysbiotic bacterial taxa including Lactobacillaceae , Streptococcaceae and others in GS individuals still needs to be elucidated.…”
Section: Discussionmentioning
confidence: 99%